2015
DOI: 10.1371/journal.pone.0122175
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienol-Rich Fraction (TRF) Suppresses the Growth of Human Colon Cancer Xenografts in Balb/C Nude Mice by the Wnt Pathway

Abstract: Tocotrienols have been shown many biologic functions such as antioxidant, anti-cancer, maintaining fertility and regulating the immune system and so on. In this study, after feeding with tocotrienol-rich fraction from palm oil (TRF) for 2 weeks, Balb/c nude mice were inoculated human colon SW620 cancer cell and then continued to feed TRF for 4 weeks. At termination of experiments, xenografts were removed and determined the expression of Wnt-pathways related protein by immunohistochemistry or western blotting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…These activities were observed commonly in the concentration range of 2 to 20 µM. The molecular mechanisms reported for the antiproliferation, proapoptosis, and other anticancer activities of δ‐T3 and γ‐T3, as depicted in Figure 3, involve the inhibitory effects on WNT signaling, 116–120 NF‐κB pathway, 121–123 NOTCH signaling, 123–126 and AKT/mTOR signaling 127,128 ; and/or the activation of STAT3, 129,130 SRC kinase, 130 AMPK, 131 and receptor tyrosine kinases HER3/HER4 132,133 . The inhibition of proliferation and induction apoptosis were also reported to be mediated through tocotrienol‐induced activation of EGR‐1/BAX pathway, 134 upregulation of miR‐34a, 125 miR‐429, 135 p27/CDKN1B, 136 and PPAR‐γ, 137 disruption of lipid raft 132,133 and modification of mitochondria membrane and activation of proapoptosis genes 138–140 .…”
Section: Laboratory Studies On Ve and Cancer Preventionmentioning
confidence: 97%
“…These activities were observed commonly in the concentration range of 2 to 20 µM. The molecular mechanisms reported for the antiproliferation, proapoptosis, and other anticancer activities of δ‐T3 and γ‐T3, as depicted in Figure 3, involve the inhibitory effects on WNT signaling, 116–120 NF‐κB pathway, 121–123 NOTCH signaling, 123–126 and AKT/mTOR signaling 127,128 ; and/or the activation of STAT3, 129,130 SRC kinase, 130 AMPK, 131 and receptor tyrosine kinases HER3/HER4 132,133 . The inhibition of proliferation and induction apoptosis were also reported to be mediated through tocotrienol‐induced activation of EGR‐1/BAX pathway, 134 upregulation of miR‐34a, 125 miR‐429, 135 p27/CDKN1B, 136 and PPAR‐γ, 137 disruption of lipid raft 132,133 and modification of mitochondria membrane and activation of proapoptosis genes 138–140 .…”
Section: Laboratory Studies On Ve and Cancer Preventionmentioning
confidence: 97%
“…Similarly, dose-dependent increase in liver catalase activity of nude male mice harvested with SW620 cells. [43] Of note, this dosedependent response of liver catalase was not observed in female mice with same treatment. [43] Contrary to these, with moderate doses of Et exposure (Et-II and Et-III), cerebellar catalase activities inclined to decrease with longer duration of T3 supplementation.…”
Section: Discussionmentioning
confidence: 86%
“…The cause of such change in cerebellar LPO level was not clear; however, with TRF supplementation, increased level of hepatic LPO was also observed in nude mice xenografted with SW620 cells. [43] Two distinct but closely related functions of catalase was imperative in the current context. Together with SOD, it forms a part of the superoxide and peroxide handling capacity (SPHC) that are produced because of Et-induced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Tocotrienols are reported to possess anti-thrombotic [120], antioxidant [121], neuroprotective [122] and cardio-protective [123] activities as well as immune modulatory [124,125] properties. Both cell-based and experimental model studies have suggested that tocotrienols also possess anti-tumor properties as these compounds can inhibit proliferation of many cancer cell lines including prostate [126], breast [127], skin [128], colon [129], stomach [130], pancreatic [131], liver [132] and lung [133] cancers. The anticancer effects induced by tocotrienol are reported to be mediated through apoptosis [134], anti-angiogenesis [135], anti-proliferative [136] and/or immunoregulation [125].…”
Section: Tocotrienolmentioning
confidence: 99%